Integration of Introduction, Development, Engagement, and Assimilation (I.D.E.A. SCHEME) to Learning Action Cell in Relation to Mental Health of Selected Senior High School Teachers in Plaridel District, Quezon, Philippines - Bhyren G. Saniel; Amor C. Castillo; Jeremias F. Masapol; Sarah Mae C. Nobleza; Jackielene V. Portea; Marlon Lamadrid; Eleanor A. Osea (International Education Trend Issues, 2023)
This study determined the proposed Learning Action Cell Scheme based on Introduction, Development, Engagement, and Assimilation in relation to the mental health of the ten selected Senior High School Teachers in Plaridel District, Division of Quezon. Using a researcher-made questionnaire distributed through Google form, it sought answers to the level of stress the Senior High School Teachers in Plaridel Quezon had the response level in the Learning Action Cell (I.D.E.A. pattern) in terms of effectivity, time management, and behavioral aspects, the acceptance level of the Learning Action Cell proposed topics and the intervention scheme for Learning Action Cell. Descriptive survey research was used. All respondents were suffering from stress attributed to various intrinsic and extrinsic stresses. Most of the respondents had had the same experiences as they underwent in the L.A.C. session. The topics proposed were useful to manage the stress level of the teachers through L.A.C. sessions and strategic leadership of the school heads.